Multiple Comparisons of Four Methods for Norovirus Detection Based on the "Sanitary Management Manual for Large Cooking Facilities" by the Ministry of Health, Labor and Welfare in Japan - OGIHARA, Shinji; INOUE, Osamu; SHOJI, Tomokazu; KUBOKAWA, Kayo; MATSUMURA, Hiroki; YAZAKI, Masahiro; INOUE-SUZUKI, Katsue (Japanese Journal of Infection Prevention and Control, 2019)
The Sanitary Management Manual for Central Kitchens legislated by the Japanese Ministry of Health, Labor and Welfare was revised on June 16, 2017. Based on the revised manual, employees in central kitchens need to undergo Norovirus testing with high sensitivity every month from October to March, which is when Norovirus outbreaks occur. In the present study, we investigated the differences among 4 methods of Norovirus testing from the viewpoints of sensitivity, user time, total examination time, and running costs. All samples obtained from 53 healthy volunteers were tested for Norovirus using the GeneXpert® system, the TaKaRa Norovirus GI/GII testing Kit, the TaqMan Probe assay, and the Quick NaviTM-Noro2. Among them, the GeneXpert® system, TaKaRa Norovirus GI/GII testing Kit, and TaqMan Probe assay were all highly sensitive, at the level required by the "sanitary management manual for large cooking facilities." The user working times of the GeneXpert, TakaRa, TaqMan, and Quick Navi testing methods for 53 samples were 106, 260, 687, and 76 min, respectively. The total examination times of the 4 were 2,434, 320, 857, and 91 min. The running costs of the 4 were 202,089, 73,644.4, 152,249, and 79,500 JPY, respectively. Based on these studies, we concluded that the TaKaRa Norovirus GI/GII testing Kit is suitable for the screen testing for Norovirus detection, and the GeneXpert® system for the follow-up testing of Norovirus-detected staff. We should understand the characteristics of the 4 methods and chose an appropriate one depending on the purpose.